Perspective of Early Childhood Education Teachers on School Connectivity to Parental Support in the Context of Blended Learning During a Pandemi - Purnamasari, Ikaningtyas; Pranoto, Yuli Kurniawati Sugiyo; Handayani, Sri Sularti Dewanti (Indonesian Journal of Early Childhood Education Studies, 2023)
Although we are now seeing a point where we can control the pandemic, its impact on education remains a major highlight. Schools around the world have been forced to make deep changes by switching to distance learning and adopting blended learning methods that integrate face-to-face and online learning. This transition not only creates challenges for students, teachers, and parents, and creates new opportunities to improve the way we educate and connect. This research explores the views of Early Childhood Education teachers in Semarang regarding School Connectedness and parent support during the pandemic. With 74 Kindergarten A and Kindergarten B teachers as participants, using the Ex post facto quantitative method in the 2021-2022 school year, this research utilized an online questionnaire via Google Forms. Ordinal regression analysis shows that parental support significantly influences School Connectedness (Wald = 7.318, sig. = 0.007). The novelty of the research lies in its focus on PAUD teachers in Semarang who are facing the challenges of distance learning and blended learning due to the pandemic. The benefits involve a deeper understanding of the crucial role of parental support in strengthening teacher-school-student relationships. The results of the research can be a basis for schools, teachers and parents to develop strategies to improve School Connectedness in the future, especially in an ever-changing learning context. Thus, this research contributes to our understanding of the factors that influence the quality of education in the pandemic era.